Immunogenicity of infectious bursal disease virus (IBDV) polyprotein expressed in silkworm as the bioreactor - LU Mi-jia; YU Lian; XIE Rong-hui; ZHANG Chao-zheng (浙江大学学报. 农业与生命科学版, 2004)
The polyprotein (VP2/4/3) gene of infectious bursal disease virus (JDl strain) was cloned into BmNPV-based vector pBacPAK8. Recombinant baculovirus BacPAK-A harbouring polyprotein gene was obtained from BmN cell co-transfected with recombinant vector and lineared genomic DNA of baculobvirus Bm-BacPAK6. BacPAK-A was used to infect fifth-instar silkworm larvae for expression of recombinant protein and haemolymph of the silkworm harvested 5-day post inoculation was emulsionized with mineral oil for immunization of 14-day old chickens. The safety trial indicated that 1-time and 5-time dose of vaccine are both safe to chickens. Groups inoculated with silkworm-expressed IBDV VP2 and normal silkworm haemolymph, respectively, were set for comparison in immunity-challenge trial. A boost was administered 14 days post primary immunization and a challenge with virulent IBDV BC6/85 25 days post the boost. Clinical and pathological protection ratio, ratio of bursa weight vs body weight, immunoprecipitation and neutrlization test were analysed. The result indicated that the polyprotein vaccine induced humoral immunity more effectively than that of the VP2 vaccine, as the former provided a more efficient protection against virulent IBDV challenge. The recombinant polyprotein could be a promising candidate for genetic engineering subunit vaccine against IBD.